PENGARUH KONTEN DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI DI TIKTOK SHOP PADA MAHASISWA PROGRAM STUDI DI MANAJEMEN UNIVERSITAS BUANA PERJUANGAN KARAWANG - Fauziah, Nur; Isyanto, Puji; Yani, Dini (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The influence of social media in the marketing field in the current era of digital technology makes social media a tool used to attract buying interest from consumers. The government implemented various policies in the era of the Covid-19 pandemic to minimize the spread of the virus, this triggered changes in the use of the internet in the community. Tiktok is a well-known media, there are many types of video content created by Tiktok users, one of which is marketing content aimed at increasing buying interest on Tiktok through the Tiktok Shop feature. In the Tiktok Shop menu there is also a review menu as a reference for buyers to obtain product information. This attraction has resulted in business players starting to look at Tiktok Shop as a platform for marketing tools. In this study, the author uses a quantitative descriptive method based on multiple linear regression analysis. The results of this study indicate that all hypotheses, digital marketing content, and electronic word of mouth have a significant and positive effect on buying interest at Tiktok Shop among students study program at the University of Buana Perjuangan Karawang. However, if without digital marketing content and electronic word of mouth, or the two independent variables are not implemented, there will be a decrease in buying interest and consumers will move to other markets. On the other hand, if digital marketing content and electronic word of mouth are implemented, all independent variables can increase buying interest at Tiktok Shop.Keywords: Digital Marketing..